Understanding Teaching Method Used in EFL Classroom: Students' and Teachers' Perspective - Rifai, Irfan; Nabhan, Salim (Universitas PGRI Adi Buana Surabaya, 2017)
This study is focused on getting an understanding of the students and teachers perceptions of teaching methods use in EFL classroom. More importantly, this research is aimed at bringing to light how students and teachers in the higher education English language classroom help provide new meanings of how different methods are used in the classrooms. To make sense of their perceptions of teaching methods, we focus on four individual narrative interviews, classroom observations and two focus group discussions. The data findings show that a particular teaching method, such as students' presentation, based on the students' view, is due to that lecturers are not quite confident to speak in front of the classroom. The students assert that the lecturers seem are not quite well prepared to teach, so that the students are asked to make presentation in front of the classroom. This, based on the students’ view is about spending much time for the students to speak rather than their lecturers’ do. In addition, the data findings illustrate that the traditional methods used in the classroom such as classroom presentation and group discussion are needed to be modified by considering the employment of technology to mediate the acquisition of 21st century skills. In addition, the findings suggest that the lecturers' experience during their careers and study deeply influence the way they conduct teaching methods in the classroom. Moreover, the data findings indicate that identity and the self- image are prevalent in shaping the teaching methods the lecturers are used in the classroom. This study indicates that students and lecturers have different view point with regards to the teaching methods use in the higher education language classroom. It is suggested, therefore, that the use of teaching methods in the classroom should ideally involve the students' view point to generate more effective and future goals oriented.